First constraints on the stellar mass function of star-forming clumps at the peak of cosmic star formation. (19th June 2018) - Dessauges-Zavadsky, Miroslava; Adamo, Angela
Abstract: Star-forming clumps dominate the rest-frame ultraviolet morphology of galaxies at the peak of cosmic star formation. If turbulence driven fragmentation is the mechanism responsible for their formation, we expect their stellar mass function to follow a power law of slope close to −2. We test this hypothesis performing the first analysis of the stellar mass function of clumps hosted in galaxies at z ∼ 1–3.5. The clump sample is gathered from the literature with similar detection thresholds and stellar masses determined in a homogeneous way. To overcome the small number statistics per galaxy (each galaxy hosts up to a few tens of clumps only), we combine all high-redshift clumps. The resulting clump mass function follows a power law of slope ∼−1.7 and flattens at masses below 2× 10^7 M_ . By means of randomly sampled clump populations, drawn out of a power-law mass function of slope −2, we test the effect of combining small clump populations, detection limits of the surveys, and blending on the mass function. Our numerical exercise reproduces all the features observed in the real clump mass function confirming that it is consistent with a power law of slope ≃ − 2. This result supports the high-redshift clump formation through fragmentation in a similar fashion as in local galaxies, but under different gas conditions.